Anaemia among lactating adolescents (15-19 years) in India: a repeated cross-sectional analysis of the NFHS data (2005-2021) - Ananya Kundu; Aditya Singh; Sumit Ram; Rakesh Chandra; Arabindo Tanti; Shivani Singh (BMC, 2024)
Abstract Background Anaemia continues to be a pressing public health concern in India. Despite the high burden of anaemia among lactating adolescents in the country, research addressing this concern among this population remains scarce. Hence, this study attempted to examine the prevalence and determinants of anaemia among lactating adolescents in India. Methods We used data from three latest rounds of the National Family Health Survey (NFHS) carried out in 2005-06, 2015-16, and 2019-21 and analysed a pooled sample of 10,689 lactating adolescents aged 15-19 years from these three rounds. Bivariate statistics was used to analyse the prevalence of anaemia according to the background characteristics of lactating adolescents. Further, binary multivariate logistic regression was carried out to examine the factors associated with anaemia in the study population. Results Three in every five lactating adolescents from the pooled sample were found to have anaemia (66.98% in NFHS-3, 61.08% in NFHS-4 and 66.27% in NFHS-5). Lactating adolescents with a higher education had a 30% lower likelihood [adjusted odds ratio (AOR): 0.70, 95% CI: 0.49-1.01, p = 0.050] of being anaemic compared to those with no education. The likelihood of being anaemic among the poorest quintile was 41% (AOR: 1.41, 1.12-1.77; p = 0.003) higher than those from the richest quintile. Lactating adolescents from the Scheduled Tribe category had higher odds (AOR: 1.29, 95% CI: 1.01-1.46, p = 0.001) of anaemia than those categorised as 'Others'. Those living in rural areas were 22% more likely to suffer from anaemia (AOR: 1.22, 95% CI: 1.00-1.26, p = 0.050) compared to their urban counterparts. Additionally, underweight lactating adolescents were 15% more likely (AOR: 1.15, 95% CI: 1.05-1.26, p = 0.002) to be anaemic than those with normal BMI. Odds of being anaemic were higher among the ones receiving supplementary nutrition during pregnancy (AOR: 1.18, 95% CI: 1.08-1.29, p < 0.001) in contrast to those not receiving. Conclusion The consistently high prevalence of anemia among lactating adolescents, especially among those with lower education level, rural residence, underweight status, and belonging to ST category and poorest quintile, underscore the urgent need for targeted public health interventions to address and reduce anemia in this population.